2022
DOI: 10.1136/bmjgh-2022-010276
|View full text |Cite
|
Sign up to set email alerts
|

Canine real-time detection of SARS-CoV-2 infections in the context of a mass screening event

Abstract: IntroductionPrevious research demonstrated that medical scent detection dogs have the ability to distinguish SARS-CoV-2 positive from negative samples with high diagnostic accuracy. To deploy these dogs as a reliable screening method, it is mandatory to examine if canines maintain their high diagnostic accuracy in real-life screening settings. We conducted a study to evaluate the performance of medical scent detection dogs under real-life circumstances.MethodsEight dogs were trained to detect SARS-CoV-2 RT-qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Vesga et al showed that dogs still performed in an acceptable way (69% sensitivity, 94% specificity) after a training gap of 2.5 months (118). Interestingly, half a week of robust "retraining" of dogs with previous COVID-19-detection experience resulted in comparable high COVID-19-detecting performance as observed after initial training (41,52,71). In contrast to the results in the study of Vesga et al (118), a recently published study highlighted that dogs indeed can remember at least 40 different defined odors, not experienced within 12 months, with 100% accuracy (131).…”
Section: Training Durationmentioning
confidence: 99%
See 4 more Smart Citations
“…Vesga et al showed that dogs still performed in an acceptable way (69% sensitivity, 94% specificity) after a training gap of 2.5 months (118). Interestingly, half a week of robust "retraining" of dogs with previous COVID-19-detection experience resulted in comparable high COVID-19-detecting performance as observed after initial training (41,52,71). In contrast to the results in the study of Vesga et al (118), a recently published study highlighted that dogs indeed can remember at least 40 different defined odors, not experienced within 12 months, with 100% accuracy (131).…”
Section: Training Durationmentioning
confidence: 99%
“…Importantly, when dogs are deployed in the field and the disease of interest has a low prevalence, reducing the opportunity for the animals to succeed in detection, positive affective and motivational states of dogs have to be sustained in order to avoid frustration (68). This can be achieved, for example, through regular rewards for the respective detection procedure or for detecting specifically prepared (positive) samples (69)(70)(71). Interestingly, variation in reward types may lead to a more pronounced maintenance of motivation in some dogs (72).…”
Section: Ethical Considerations For Using Detection Dogsmentioning
confidence: 99%
See 3 more Smart Citations